Harapan Pasien Kanker Payudara yang Mendapat Kemoterapi Tentang Dukungan Keluarga - Ni Ketut Kardiyudiani (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2013)
Background: Breast cancer is carcinoma or malignancy in some morphology as well, and one kinds of treatment that is given is chemotherapy. There were various kinds of nursing strategy to help overcoming various effects that are aroused by the chemotherapy given including family support. Therefore, the purpose of this research was to explore deeper about family support in raising breast cancer patient’s hope which is got chemotherapy. This research is held toward five participants and find four themes i.e. hope to continue normal life in their family, hope to raise family understanding about the impact malady caused by chemotherapy, hope to be appreciated, to be listened and to be accompanied, hope to be helped by their family in overcoming a problem which is faced because of the disease. Methods: The design of this research study uses a qualitative method of phenomenology is an approach to learn the meaning of the human experience of undergoing a phase in his life. Observation methods in-depth interviews conducted by researchers simultaneously to participants, as well as interviews from other sources such as care giver. Researcher uses himself as a means of collecting data, using in-depth interviews (indept interview). Interviews conducted no more than 30-60 minutes. Closed when the information has been obtained in accordance with the research objectives. Researchers maintain that no judgment against participants from previous participants' understanding. Researchers writing non-verbal expressions are important participants in favor of expression participants using field notes. Field notes to document the use of non-verbal participants, the atmosphere during the interview for later incorporated in the transcript. Result: The results of this study are in the form of theme. Themes found after analysts thematic and found there are 4 themes: 1) the theme to resume normal activities within a family, 2) improved understanding of the family theme of the impact of chemotherapy due to disease and treatment, 3) theme hopes to be appreciated, listened to, and accompanied, 4 ) theme help solving problems faced due to illness.